2010
DOI: 10.1111/j.1748-5967.2010.00296.x
|View full text |Cite|
|
Sign up to set email alerts
|

Biology of Bactrocera (Zeugodacus) tau (Walker) (Diptera: Tephritidae)

Abstract: The biology of the fruit fly Bactrocera tau, an important horticultural pest, was studied under laboratory conditions at 25°C and 60–70% relative humidity on Cucurbita maxima. The duration of mating averaged 408.03 ± 235.93 min. After mating, the female fly had a preoviposition period of 11.7 ± 4.49 days. The oviposition rate was 9.9 ± 8.50 eggs and fecundity was 464.6 ± 67.98 eggs/female. Eggs were elliptical, smooth and shiny white, turning darker as hatching approached, and measured 1.30 ± 0.07 mm × 0.24 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
30
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 8 publications
(8 reference statements)
12
30
2
Order By: Relevance
“…The present observations are in corroborated with the earlier findings of Singh et al, (2010), who reported 3.8±0.074mm x 0.55±0.10mm and 8.02±1.02 mm x 1.55± 0.17 mm for fresh and full grown maggots respectively.…”
Section: Maggotssupporting
confidence: 93%
See 4 more Smart Citations
“…The present observations are in corroborated with the earlier findings of Singh et al, (2010), who reported 3.8±0.074mm x 0.55±0.10mm and 8.02±1.02 mm x 1.55± 0.17 mm for fresh and full grown maggots respectively.…”
Section: Maggotssupporting
confidence: 93%
“…The pre-oviposition period was observed between 10 to 14 days, with a mean duration of 12.1±1.28 days. These findings are in agreement with the findings of Singh et al, (2010).…”
Section: Reproductionsupporting
confidence: 93%
See 3 more Smart Citations